2020
DOI: 10.1093/ehjqcco/qcaa054
|View full text |Cite
|
Sign up to set email alerts
|

COMPASS criteria applied to a contemporary cohort of unselected patients with stable coronary artery diseases: insights from the START registry

Abstract: Background Recently, the COMPASS trial demonstrated that dual therapy reduced cardiovascular outcomes compared with aspirin alone in patients with stable atherosclerotic disease. Methods and Results We sought to assess the proportion of patients eligible for the COMPASS trial and to compare the epidemiology and outcome of these patients with those without COMPASS inclusion or with any exclusion criteria in a contemporary, nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
(44 reference statements)
0
4
0
1
Order By: Relevance
“…After applying the inclusion/exclusion criteria of the COMPASS trial to the population (n = 31,873) of the large international REduction of Atherothrombosis for Continued Health (REACH) registry, 53% of patients were found to be eligible for the COMPASS strategy [18]. In a recent analysis of a nationwide cohort, 44.5% of 4068 patients were classified as COMPASSlike patients [19]. Compared to our results, in both cases, the proportion of potentially eligible patients appears to be lower.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After applying the inclusion/exclusion criteria of the COMPASS trial to the population (n = 31,873) of the large international REduction of Atherothrombosis for Continued Health (REACH) registry, 53% of patients were found to be eligible for the COMPASS strategy [18]. In a recent analysis of a nationwide cohort, 44.5% of 4068 patients were classified as COMPASSlike patients [19]. Compared to our results, in both cases, the proportion of potentially eligible patients appears to be lower.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these data and the prevalence of risk factors in our real-life population with COMPASS phenotype, we can speculate that the cardiovascular benefits observed in the trial could be amplified in realworld clinical scenarios. In a previous study by De Luca et al [19], comparing patients meeting 1 with those meeting ≥3 COMPASS criteria, showed that patients with multiple criteria had a significantly high risk of MACE (from 1.0% to 3.3%, p = 0.012) and a modest absolute increase in the risk of major bleeding (from 0.2% to 0.4%, respectively; p = 0.46) [19].…”
Section: Discussionmentioning
confidence: 99%
“…In the real-world setting, the proportion of COMPASS-Eligible Patients in the REACH 16 and italian START (STable Coronary Artery Diseases RegisTry) 17 registries are well represented, in fact they are about half (52,9% in REACH and 44,5% in START Registry) ( Figure 7 ). In particular, in both registries, ischaemic outcome increased according to the number of enrichment criteria, without a significant change of safety profile (disproportionate increase in ischaemic vs. bleeding risk in patients with multiple enrichment criteria).…”
Section: Effects Of Low-dose Rivaroxaban In Real-world Cohortsmentioning
confidence: 99%
“…In COMPASS-Like population, patients with multiple enrichment criteria at inclusion (diabetes mellitus, age >65 years, asymptomatic carotid disease, PAD, history of heart failure, renal impairment, current smoking status, and history of ischaemic stroke) presented a significant increase in the risk of major adverse events, and a modest absolute increase in the rate of major bleedings. 16 , 17 Accordingly, in a post hoc analysis of the COMPASS trial subjects were classified as high-risk according to REACH scoring (two or more vascular beds affected, history of heart failure, or renal insufficiency) or CART scoring (two or more vascular beds affected, history of heart failure, or diabetes) 18 Those with high-risk features presented a lower incidence of major adverse CV events, acute limb ischaemia, or total vascular amputation when treated with DPI compared with ASA, with a similar rate of major bleeding events.…”
Section: Effects Of Low-dose Rivaroxaban In Real-world Cohortsmentioning
confidence: 99%
“…в результате из-за опасений увеличения риска кровотечений в реальной клинической практике при выборе антитромботической терапии для больных высокого ишемического риска в сочетании с хбп часто применяется не двойная терапия, а монотерапия ацетилсалициловой кислотой. данные большого регистра больных с ибС указывают на то, что около половины больных реальной клинической практики соответствует критериям включения, которые использовались в рки COmpAss, и им показана комбинированная терапия ривароксабаном и ацетилсалициловой кислотой [72].…”
Section: выбор антитромботической терапии у больных сд 2 типа после п...unclassified